Studies in the Contract Laws of Asia, Volumes I–III - Nottage, Luke (Zeitschrift für Japanisches Recht, 2022)
Studies in the Contract Laws of Asia, Oxford, Oxford University Press: Mindy Chen-Wishart / Alexander Loke / ‌Burton Ong (eds.), Remedies for Breach of Contract, Vol. I (2016), £97.00. Mindy Chen-Wishart / Alexander Loke / Stefan Vogenauer (eds.), Formation and Third Party Beneficiaries, Vol. II (2018), £110.00. Mindy Chen-Wishart / Stefan Vogenauer (eds.), Contents of Contracts and Unfair Terms, Vol. III (2020), £125.00.